Antioxidant and antibacterial activity of Allium saralicum and Allium longisepalum leaves extracts as medicinal plants in Iran - Choobkar, Nasrin; Aghajani, Abdoreza; Kakoolaki, Shapour; Amini Geram, Pooneh; Rezaeemanesh, Mahya (Researcher Bulletin of Medical Sciences, 2021)
Recently, there has been increasing interest in medicinal plants, due to their content of health-promoting compounds, e.g., phenolics. Hence, this study aims to estimate the antioxidant and antibacterial properties of Soraneh (Allium saralicum R.M. Fritsch) and Pichkeh (Allium longisepalum) extracts as a Iranian medicinal plants. The study was done by 2,2-diphenyl-2-picrylhydrazyl (DPPH) assays, total phenolic content, total flavonoid content and antibacterial effects of the herbal extracts were determined. According to results, the highest total phenolic content (1.187±0.012mgGAE/g) was obtained in aqueous extract of Pichkeh. The highest total flavonoid content (1.193±0.004mgRE/g) and the antioxidant activity (5.93±0.07%) were found for hydroalcoholic extract of Soraneh and Pichkeh, respectively. In disk-diﬀusion test, for two extracts, the highest and lowest antibacterial effect was observed for L. monocytogenes and S. aureus, respectively. Soraneh extract had the highest and the lowest antibacterial effect on L.monocytogenes and P. aeruginosa, respectively. In the well-diﬀusion method, Pichkeh extract had the highest antibacterial effect on S.aureus. For the Soraneh extract, the highest effect was related to B. cereus, and there was also no detectable colony of S.aureus, P.aeruginosa and S. enterica. The results of present comprehensive analysis demonstrated that Soraneh and Pichkeh leaves possess high phenolic, flavonoid contents and potential antioxidant and antibacterial activity, and could be used as a viable source of bioactive compounds and might be exploited for functional foods and neutraceutical applications.